CONCEPT OF JARA AND ITS MANAGEMENT THROUGH KSHARA POTENTIATED RASAYANA - Vivek Singh; Rapolu Sunil B (International Journal of Applied Ayurved Research, 2015)
Ayruveda, the science of life covers a wide range of subjects and issues of living beings in relation to total approaches of individual development and health care. Different Ayurvedic literature preaches wide and in depth knowledge of ideal living including primitive, preven-tive and curative aspect of health sciences. Jara (aging) management in present time is a challenging task for present health providing system. Our ancestral knowledge helps to tackle these challenges through kshara potentiated rasayana.